Propagation of megawatt subpicosecond light pulses with the minimum possible shape and spectrum distortion in an air- or argon-filled hollow-core revolver fibre. (December 2019) - Gladyshev, A.V.; Yatsenko, Yu.P.; Kosolapov, A.F.; Myasnikov, D.V.; Bufetov, I.A.
Abstract: We have examined the feasibility of undistorted subpicosecond pulse transmission at peak powers of up to 100 MW and a wavelength of 1030 nm in a hollow-core revolver fibre having a core filled with atmospheric air or argon. A hollow-core revolver fibre has been fabricated which has a low-dispersion ( β 2 ≈ – 0.25 ps 2 km −1 ) transmission band in the spectral range of ytterbium and neodymium lasers. Conditions for the nonlinear (soliton) regime of megawatt picosecond pulse propagation over up to 1-km lengths of revolver fibre in atmospheric air and argon at pressures in the range 10 −5 to 1 atm have been found theoretically. We have experimentally demonstrated transmission of pulses of 0.8-ps duration and up to ∼100-MW power over an ∼3-m length of revolver fibre with the minimum possible distortion of their shape and spectrum.